Osseocartilaginous metaplasia in the Endometrium: A Rare Reversible Cause of Secondary Infertility - Senapati, Swagatika; Mahawar, Shruti; Pani, Krushna Chandra (Annals of Pathology and Laboratory Medicine, 2022)
Osteo-cartilaginous metaplasia in endometrium is an infrequent finding and usually presents with secondary infertility. This is a benign entity and usually associated with a previous history of abortion. It can be treated successfully with hysteroscopy and henceforth reverting infertility. Awareness of this entity is important in order to avoid overdiagnosis of mixed Mullerian tumor of the endometrium followed by hysterectomy. Herein, we present one such case of a 28-year-old female who presented with secondary infertility.